In a mouse model relevant for PTSD, selective brain steroidogenic stimulants (SBSSs) improve behavioral deficits by normalizing allopregnanolone biosynthesis - Pinna, Graziano (2010)
The pathophysiological role of the neurosteroid 3α-hydroxy-5α-pregnan-20-one (allopregnanolone) in neuropsychiatric disorders has been highlighted in several recent investigations. For instance, allopregnanolone levels are decreased in the cerebrospinal fluid (CSF) of patients with posttraumatic stress disorder (PTSD) and major unipolar depression. Neurosteroidogenic antidepressants, including fluoxetine and analogs, correct this decrease in a manner that correlates with improved depressive symptoms. PTSD-like behavioral dysfunctions, including heightened aggression, exaggerated fear, and anxiety-like behavior associated with a decrease in corticolimbic allopregnanolone content are modeled in mice by protracted social isolation stress. Allopregnanolone is not only synthesized by principal glutamatergic and GABAergic neurons but also locally, potently, positively, and allosterically modulates GABA action at post- and extra-synaptic GABA(A) receptors. Hence, this paper will review preclinical studies which show that in socially-isolated mice, rather than SSRI mechanisms, allopregnanolone biosynthesis in glutamatergic corticolimbic neurons offers a non-traditional target for fluoxetine to decrease signs of aggression, normalize fear responses, and decrease anxiety-like behavior. At low SSRI-inactive doses, fluoxetine and related congeners potently increase allopregnanolone levels by acting as potent selective brain steroidogenic stimulants (SBSSs), thereby facilitating GABA(A) receptor neurotransmission and improving behavioral dysfunctions. Although the precise molecular mechanisms that underlie the action of these drugs are not fully understood, findings from socially-isolated mice may ultimately generate insights into novel drug targets for the treatment of psychiatric disorders, such as anxiety and panic disorders, depression, and PTSD.